The experience of back pain in young Australians - McMeeken, J.; Tully, E.; Stillman, B.; Nattrass, C.; Bygott, I. L.; Story, I. (2001)
The usual activity level and history of low back pain was determined by questionnaire in 614 young Australians (9-27 years); dancers (25%), gymnasts (5%) and a control group who did not participate in dance or gymnastics for >/=6 hours/week during the previous three months (70%). These groups demonstrated significantly different activity levels (dancers >gymnasts >controls). Of all respondents, 34% experienced pain of more than two days duration in the previous year, and 50% in all previous years. The incidence and magnitude of pain in the previous year was significantly greater in the dancers and gymnasts (P<0.05) compared to the controls. The incidence of pain was not linked to the average total hours of activity until this exceeded 30 hours per week. There was no significant difference in the incidence of pain in the previous year between control group respondents who did and did not undertake regular activity. The average hours of activity per incident was approximately 20 hours for the dancers and approximately 5 hours for the other groups. This study has demonstrated that back pain in active and inactive adolescents presents a significant challenge for health-care practitioners involved in the management and prevention of symptomatic spinal disorders. Man Ther 2001 Nov;6(4):213-20